Global Responses to Conflict and Crisis in Syria and Yemen - Guidero, Amanda. author. aut Link
XIII, 118 p. 8 illus. in color.
Keywords: “Why is Syria getting so much more attention than Yemen? This book explores an acute discrepancy of attention in coverage of humanitarian crises, so we can ask with greater precision why some human beings seem to be valued more than others in our troubled world.” —Joseph G. Bock, Director, School of Conflict Management, Peacebuilding and Development, Kennesaw State University, USA This book compares different international responses to the internal conflicts in Syria and Yemen through an examination of the coverage each conflict has received in the media. The work explores and evaluates rival explanations for why the Syrian conflict has garnered so much more attention than the Yemen conflict and the opportunities and limitations for using international law and international humanitarian law to discuss and analyze intervention. Using this assessment, the authors discuss why this differential attention matters in terms of IR theory, humanitarian response, and policy recommendations for responding to humanitarian crises. Amanda Guidero is Assistant Professor in the Department of Interdisciplinary Studies and Instructor in the Negotiation and Conflict Resolution program at Creighton University, USA. Maia Carter Hallward is Professor of Middle East Politics in the School of Conflict Management, Peacebuilding and Development at Kennesaw State University, USA.